Numerical and Experimental Study of the Performance of Electromagnetic Flowmeter in Annular Flow - Jawaad, Ihsaan Nadhum; Ismael, Muneer A. (Basrah Journal for Engineering Sciences, 2014)
The present numerical and experimental work investigates the performance of electromagnetic flowmeter (EMF) for measuring the flow rate of annular flow. Adaptive finite difference technique is used for the numerical calculations and the experimental work is done by making some modification on an existing electromagnetic flowmeter and its testing rig. The performance of the modified EMF is evaluated using two criteria namely, the flowmeter sensitivity S and the conventional weight function non uniformity ε. These two criteria were checked against two parameters; thickness of flowing water (δ) and the electrodes angular position (θe). Experimentally, three different water thickness (δ/Ro = 0.216, 0.373, 0.218) and three electrode position (θe=0o, 11.25o, 45o) were studied. The theoretical and experimental results have showed that these devices work properly in the annular flow case, where the most suitable electrode position in the annular flow was found to be in the conventional position (θe =0o).